Genetic diversity analysis of Indonesian soybean genotypes based on morphological characteristics and SSR markers - Tasma, I Made (2026)
Introduction. Soybean is an important crop due to its high protein and oil content. Yellow-seeded varieties are preferred for the production of food products. Analyzing genetic diversity is a crucial step in selecting parental lines for breeding programs. Objective. To analyze the genetic diversity of Indonesian soybean genotypes using morphological characteristics and simple sequence repeat (SSR) markers. Materials and methods. Field evaluations were conducted in Bogor, Indonesia, from March to June 2023. Morphological data were analyzed using principal component analysis (PCA) and principal coordinate analysis (PCoA). Subsequently, the genotypes were analyzed using 14 SSR markers. Results. PCA revealed that PC1-PC4 explained 72.63 % of total genetic variation. SSR marker analysis demonstrated excellent characteristics such as a high number of alleles and favorable PIC values. Genotypes were grouped into two clusters with a clear genetic distinction. Four genotype pairs exhibited high genetic diversity with favorable morphological traits related to yield and its components. These genotype pairs represent potential parental candidates for soybean breeding programs. Conclusions. Morphological and SSR marker characterizations clearly differentiated Indonesian soybean genotypes and identified genotype pairs with high genetic diversity that were suitable as parental candidates for breeding purposes. Both data analyses provided complementary information, resulting in a more comprehensive assessment of genetic diversity.